MANAJEMEN PENDIDIKAN ANAK USIA DINI DI RA AR ROHMAN KOTA BATU - Setiawan, Eko; Cahyani, Fariza Ika (Jurnal Caksana : Pendidikan Anak Usia Dini, 2022)
Education for early childhood is being discussed because many opinions reveal that the management of early childhood education institutions is in a bad state. This attracted the attention of researchers to find out directly whether the statement was true or not, and decided to conduct research in RA Ar Rohman Batu City. This study aims to determine the management of education in RA Ar Rohman Batu City. This study uses data collection techniques in the form of interviews and documentation. This study uses a descriptive method with a qualitative approach. The results showed that RA Ar Rohman had implemented well the management of education in schools based on what was stipulated in the National Standard.